Early postoperative interventions in the prevention and management of thyroidectomy scars - Hong, Nan; Sheng, Bin; Yu, Pan (Frontiers in Physiology, 2024)
Thyroidectomy scar, locating on exposed site, can cause distress in patients.Owing to the cosmetic importance of thyroidectomy scar, many studies have been conducted on its prevention and treatment. Scar formation factors mainly include inflammatory cell infiltration, angiogenesis, fibroblast proliferation, secretion of cytokines such as transforming growth factor (TGF)-β1, and mechanical tension on the wound edges. Targeting these scar formation factors, anti-scar methods including topical anti-scar agents, skin tension bearing devices, local injections of botulinum toxin, as well as lasers and photo therapies, have been developed. However, current studies remain fragmented and there lacks a comprehensive evaluation of the impacts of these anti-scar methods on treating thyroidectomy scar. Early intervention is a crucial but often neglected key to control hyperplastic thyroidectomy scar. Therefore, we review the currently adopted early postoperative strategies for thyroidectomy scar reduction, aiming to illustrate the mechanism of these anti-scar methods and provide flexible and comprehensive treatment selections for clinical physicians to deal with thyroidectomy scars.